The prevalence of glaucoma in young people: findings of the population-based Gutenberg Health Study - Marx-Groß, Susanne; Mirshahi, Alireza (Deutsches Ärzteblatt, 2017)
Background: Earlier information on the prevalence of glaucoma among children in Germany was based solely on estimates. Reported values for congenital glaucoma range from 1 in 10 000 to 1 in 68 000 depending on ethnic origin. The estimate for juvenile glaucoma is 1 in 44 000. Methods: The Gutenberg Health Study is a population-based, prospective, monocentric cohort study with 15 010 participants aged 35 to 74. To determine the history-based prevalence of childhood glaucoma, participants were asked about the diagnosis of glaucoma, any operations for glaucoma that were performed, regular use of drugs for glaucoma, and the age of onset of glaucoma. The affected individuals were classified in four groups based on the age of onset: congenital (<2 years), juvenile (2 to <18 years), late juvenile (18 to <40 years), and early adult (40 to <45 years). In the identified glaucoma patients, the visual acuity, intraocular pressure, corneal thickness, visual fields, and optic discs were evaluated. Results: 352 persons were identified from their medical history as having glaucoma. The weighted prevalences in the four groups were 0% in the congenital group, 0.01% (95% confidence interval [0, 0.03]) in the juvenile group, 0.16 % ([0.09; 0.23]) in the late juvenile group, and 0.17% ([0.15; 0.19]) in the early adult group. For participants over age 45, the weighted prevalence of glaucoma was 1.98% [1.7; 2.2]. Conclusion: In our cohort, the history-based prevalence of juvenile glaucoma was 0.01% (2 patients). The prevalence was an order of magnitude higher (0.16%) between the ages of 18 and 40, and two orders of magnitude higher at later ages (1.98%). The burden of disease seems to be markedly higher than previously assumed.